Evaluation of Conjunctival Autografting Augmented with Mitomycin C Application versus Ologen Implantation in the Surgical Treatment of Recurrent Pterygium - Faried M. Wagdy; Hassan G. Farahat; Amin F. Ellakwa; Sameh S. Mandour (Journal of Ophthalmology)
Objectives. To evaluate the safety and efficacy of augmenting conjunctival autografting with intraoperative mitomycin C (MMC) application versus Ologen implantation in the management of recurrent pterygium. Materials and Methods. This prospective randomised study included 63 eyes of 63 patients, with recurrent nasal pterygium, who presented to the outpatient clinic of Menoufia University Hospital in Shebin El Kom and Manshiet Soltan from January 2016 to December 2019. Patients were randomly enrolled into two groups. Group A included 32 eyes of 32 patients who underwent conjunctival autografting augmented with the topical application of MMC (0.2 mg/mL), and group B included 31 eyes of 31 patients who underwent conjunctival autografting augmented with Ologen implantation. All the patients underwent follow-up examinations for a period of 24 months. During each visit, a complete ophthalmic examination was performed. Pterygium regrowth of 1 mm or more, over the cornea, was considered a recurrence. Results. In the MMC group, no recurrence was reported during the 24-month follow-up period. In the Ologen implantation group, recurrence was reported in 2 (8%) eyes. The time interval from surgery to recurrence was 5 months in one case and 8 months in the other. No other serious postoperative complications were reported, and there was no statistically significant difference between the groups in this regard. Conclusion. Ologen implantation with conjunctival autografting shows promising results in the surgical management of recurrent pterygium with mild non-vision-threatening postoperative complications comparable to that of MMC application with conjunctival autografting. Registration number: ClinicalTrials.govNCT04419038.